2003
DOI: 10.1128/jvi.77.12.7131-7138.2003
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis versus Inhibition in the Efficiency of Extinction of Foot-and-Mouth Disease Virus

Abstract: RNA viruses replicate near the error threshold for maintenance of genetic information, and an increase in mutation frequency during replication may drive RNA viruses to extinction in a process termed lethal mutagenesis. This report addresses the efficiency of extinction (versus escape from extinction) of foot-andmouth disease virus (FMDV) by combinations of the mutagenic base analog 5-fluorouracil (FU) and the antiviral inhibitors guanidine hydrochloride (G) and heparin (H). Selection of G-or H-resistant, exti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
129
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4
1

Relationship

5
4

Authors

Journals

citations
Cited by 93 publications
(134 citation statements)
references
References 57 publications
(89 reference statements)
5
129
0
Order By: Relevance
“…These genomes include cellular structures and viral proteins (i.e., polymerase and structural proteins of the capsid and envelope). Because of the high error rates of RNA viruses, even inside a single cell, the genetic diversity can be very large, because mutants with a reduced ability to replicate or encode functional proteins are continuously generated (12). However, as long as functional products that can act in trans are accessible for any genome in the cellular interior, there is nothing limiting their use by defective mutants unable to code for correct proteins themselves.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These genomes include cellular structures and viral proteins (i.e., polymerase and structural proteins of the capsid and envelope). Because of the high error rates of RNA viruses, even inside a single cell, the genetic diversity can be very large, because mutants with a reduced ability to replicate or encode functional proteins are continuously generated (12). However, as long as functional products that can act in trans are accessible for any genome in the cellular interior, there is nothing limiting their use by defective mutants unable to code for correct proteins themselves.…”
mentioning
confidence: 99%
“…This phenomenon is known as error catastrophe. The high mutation rate of RNA viruses places viral quasispecies very close to the error threshold (5,6), and it has been experimentally demonstrated that small increases of mutation rate through the use of mutagens can force the extinction of viral populations (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Classical theories on error catastrophe equal fitness to replicative ability and explain extinction on the basis of the accumulation of many deleterious mutations in the viral genomes, so that they eventually fail to replicate themselves.…”
mentioning
confidence: 99%
“…It has been shown that a combination of mutagenic agents and antiviral inhibitors is an efficient way to drive FMDV to extinction (13,14). The mutagen succeeds in raising the fraction of defective and lethal mutants in the population, thus decreasing its overall fitness.…”
mentioning
confidence: 99%
“…This unique biochemical activity and the high mutation rate of RNA viruses have stimulated the interest in the use of mutagenic rNTP analogs to induce virus entry into error catastrophe. Among them, ribavirin (1-␤-D-ribofuranosyl-1,2,3-triazole-3-carboxamide) and 5-f luorouracil have been shown to drive different RNA viruses to extinction through enhanced mutagenesis, including foot-and-mouth disease virus (FMDV) (4)(5)(6)(7)(8)(9)(10)(11). Structural studies on replicative complexes of viral RDRPs, template-primers, and rNTP substrates or analogs are needed to understand the molecular basis of the low fidelity of copy of these enzymes and the mutagenic activities displayed by rNTP analogs on viral replication.…”
mentioning
confidence: 99%